(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
The pumpkin (Cucurbita sp.) It has attractive qualities to make food beneficial to health. There are not studies related to the use of this vegetable in laminates. From here derives the expectation if they would present appropriate characteristics for their consumption. Therefore, the physical-chemical and sensory characteristics of laminates made with pumpkin pulp were evaluated. A puree with pumpkin pulp, natural thickener, sucrose, fructose, maltodextrin, citric acid and ascorbic acid was prepared, spread on trays 3 mm thick and dehydrated at 60 ° C. Four treatments were developed using a 2x2 factorial design, varying the proportions of pulp: soluble solids (75:25 and 70:30) and pumpkin pulp: natural thickener (50:50 and 55:45). Evaluating the acceptability of laminates using a 7-point structured hedonic scale. The acceptability of sensory attributes sweetness, acidity, hardness when biting and pumpkin flavor was determined by a JAR (just-about-right) 3-point scale. Acceptability varied between 5.34 and 5.7, without significant statistical effect of the two factors studied on the level of liking. The low sweetness and low pumpkin flavor were the descriptors that affected the acceptability. The treatment with a proportion of 70:30 pulp: soluble solids and 55:45 pumpkin pulp: commercial natural thickener represented the best option, due to the greater contribution of soluble solids and pumpkin pulp, together with the consumer’s liking, which generated laminates with acidity of 5.18 g citric acid / 100 g, pH of 3.44, humidity of 21.01%, 0.5% of ashes and 61.13 ° Brix in soluble solids.